Factor Structure of the Short-Form of Center for Epidemiological Studies Depression Scale for People With Physical Disabilities - Park, Eun-Young (Frontiers in Psychiatry, 2021)
This study aimed to examine the factor structure of the short-form of Center for Epidemiological Studies Depression Scale (CES-D-11) using confirmatory factor analysis (CFA). We extracted data from 670 people with physical disabilities (PWPD) from the Korea Welfare Panel. To investigate the model fit regarding factor structure, a one-factor model, four-factor model, and four-factor within bifactor model, as reported in previous studies, were examined using CFA, and goodness-of-fit indices were compared. As a result of the analysis, the four-factor model and the four-factor within bifactor model satisfied the criteria of correspondence with goodness-of-fit indices. Reliability of the four individual factors ranged from .722 to .834, indicating acceptable reliability. Validity and reliability of the four-factor within bifactor structure was confirmed through CFA and reliability analysis. In future studies using the CES-D-11 to measure depression in PWPD, comparison between four sub-factors and total scores might be possible.